AN ANALYSIS OF ORAL CORRECTIVE FEEDBACK TO SCAFFOLD STUDENTS IN LEARNING SPOKEN ENGLISH - Tersta, Friscilla Wulan (2017)
This study attempts to portray types of oral corrective feedback that is frequently used to scaffold students in learning spoken English and to investigate how scaffolding oral corrective feedback influences the students' improvement in spoken English. Oral corrective feedback has been often considered as a correcting tool for students' errors. However, there are some potentials that corrective feedback could be scaffolding to students' learning. This study used qualitative data collection and analysis. Relying on the data in the form of classroom observation field notes, students' scores, and students' exercises, this study analyzed the collected data to find the teacher's trend in providing corrective feedback, and to find the students' improvement in learning as a result of the teacher's corrective feedback. The analysis showed that explicit correction was the most frequently used corrective feedback from the teacher to scaffold his students in learning spoken English. In addition, the students' improvement was identified in their more solid understanding of grammar aspects from one stage to another stage of learning spoken English. This study suggests that teachers need to get familiar with scaffolding feedback to result in positive input; therefore, students can develop their own capacity in learning.